2001
DOI: 10.1007/s11745-001-0661-4
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term seal‐ and cod‐liver‐oil supplementation in hypercholesterolemic subjects

Abstract: In this long-term study, we wanted to explore the effect of dietary supplementation of seal oil (SO) as compared cod-liver oil (CLO) on subjects with moderate hypercholesterolemia. The test parameters included fatty acid composition in serum, blood lipids, platelet aggregation, and the activity of blood monocytes. After a run-in period of 6 mon, 120 clinically healthy hypercholesterolemic (7.0-9.5 mmol/L; 270-366 mg/dL) subjects were randomly selected to consume either 15 mL of SO or CLO daily for 14 mon follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Results of previous studies with fish oil supplementation have been mixed for apoB100: two studies have found decreases in dyslipidemic subjects [40][41] and two studies demonstrated increases in healthy individuals and individuals with CVD risk factors [42][43] . We speculate that the enhanced catabolism of very-low density lipoprotein with n-3 PUFA supplementation may have slightly increased the conversion to intermediate density lipoprotein and LDL, confirmed by the trend of the rise in LDL-C, and this is more apparent in healthier individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies with fish oil supplementation have been mixed for apoB100: two studies have found decreases in dyslipidemic subjects [40][41] and two studies demonstrated increases in healthy individuals and individuals with CVD risk factors [42][43] . We speculate that the enhanced catabolism of very-low density lipoprotein with n-3 PUFA supplementation may have slightly increased the conversion to intermediate density lipoprotein and LDL, confirmed by the trend of the rise in LDL-C, and this is more apparent in healthier individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the 2 studies on primary prevention by Brox et al [204] and Malaguarnera et al [205] quoted therein are not contained in their publications [204,205] (LOE Ib); a presentation in the work of Hooper et al [25] shows that both studies have an extremely small size and number of cases (1 cardiovascular event in each study).…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intake mentioning
confidence: 99%
“…When the results of the DART II Study were excluded, the effect estimates for CHD mortality or fatal myocardial infarction were statistically significant. The 2 individual studies on primary prevention were the one already quoted above by Yokoyama et al [206] (LOE Ib) and the unpublished results of the study by Brox et al [204] (LOE Ib), neither of which showed any significant results.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intake mentioning
confidence: 99%
“…The level of EPA, a marker of the intake of marine fatty acids, was very low in both groups, both at the entry of the study and after 1 y of follow-up. The EPA level was about 25% of that in adults from the coastal region, and only 5 -10% of the level achieved after daily ingestion moderate amounts (15 ml) of cod liver oil (Brox et al, 2001). The daily intake of vitamin D was also low (Table 3), confirming the small consumption of fish and marine lipids.…”
Section: Total Fatty Acidsmentioning
confidence: 86%
“…Considering the health-promoting effects of EPA and intake of fish and marine lipids, with respect to prevention of coronary heart disease, coronary events and blood vessel occlusion (Schmidt & Dyerberg, 1994;Burr et al, 1989;Gissi-Prevenzione Investigators, 1999;Eritsland et al, 1996), it is worrying that adolescents of 13 -15 y hardly consume marine fatty acids. Docosahexaenoic acid (DHA,22:6,, in contrast to EPA, was found at similar levels those in adults (Brox et al, 2001), indicating biological preference for this fatty acid. DHA is vital in the development of the central nervous system (Uauy et al, 2000;Youdim et al, 2000).…”
Section: Total Fatty Acidsmentioning
confidence: 89%